Whatsapp Messenger as a Mobile Media to Learn Writing for EFL Students - Linda Linda; Ida Ri'aeni (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
Abstract The objective of this research is to find out the use of Whatsapp Messenger as a mobile media to learn writing in EFL classes.Several researchers have attempted to prove applicability of mobile learning as modern ways of teaching and learning (Naismith, 2004:115). Moreover, applying portable technologies have been demanded by most of the modern learners who oftentimes are forced to study anywhere, and anytime, for example, at work, in the bus or at weekends (Evans, 2008:115).The research was motivated by the students’ difficulties in writing. The sample of this research was three classes of first grade students of English Department of Unswagati. The instrument of this research was questionnaire sheet. Data from questionnaire sheet was analyzed based on the frequency students’ answers and then was calculated and interpreted into percentages. The result shows WhatsApp Messenger attracts the students interest and also the students have positive responses towards the using ofWhatsAppMessenger. In applying WhatsApp group, the writer concluded that, learning using WhatsApp group has effective to develop their creativity in writing skill. On the other hand, the result from the questionnaire sheet indicated that almost of students is active in learning to writing recount text. Students can learn out of the classroom. Beside WhatsApp can be used privately, it can be used for students’ education. The students can use their gadget positively for their ability in learning English. The students can improve their knowledge in learning ICTs (Information and Communication Technologies). Keyword: WhatsApp Messenger,EFL writing, Instructional Media, ICTs (Information and Communication Technologies).